Enzyme- and cell-mediated degradation of poly(ethylene carbonate) by surface erosion. (January 2019) - Bohr, Adam; Memarzadeh, Kaveh; Harmankaya, Necati; Beck-Broichsitter, Moritz
Abstract: Poly(ethylene carbonate) (PEC) is a biodegradable polymer with attractive properties for controlled drug delivery applications. However, the mechanisms by which the polymer is degraded and the control hereof are not yet completely understood. Here, we investigated the degradation behavior of PEC films in vitro in the presence of distinct enzymes, cells, bacteria and tissue homogenates. PEC was degraded by a surface erosion process (constant molecular weight with an almost linear mass loss during incubation). Of the enzymes tested, only cholesterol esterase from porcine pancreas and lipase from Thermomyces lanuginosus caused significant polymer erosion. Enzymatic degradation was arrested by the addition of a protease inhibitor cocktail. Furthermore, PEC films, which were exposed to the macrophage cell lines RAW 264.7 and J774.1 showed a rapid degradation profile. The polymer erosion process triggered by phagocytes was dose-dependently diminished in the presence of vitamin C. When PEC films were incubated with pancreas homogenate no measurable degradation by mass was detected. However, scanning electron microscopy analysis showed signs of erosion on the surface of the polymer samples. Overall, this study identified specific enzymes, cells and organ homogenates, which degraded PEC in vitro and thus, should be involved in the clinical picture to facilitate an on-demand drug release at the diseased site of action. Application of enzyme inhibitors and antioxidants further highlighted the relevant role of radicals during macrophage-triggered degradation of PEC. Graphical abstract: